Analyzing stock returns in Indonesian state-owned firms: NPM, ROE and GCG factors - Markonah, Markonah; Riwayati, Hedwigis Esti (International Journal of Innovative Research and Scientific Studies, 2024)
This research aims to investigate the factors influencing the stock returns of state-owned enterprises (SOE) in Indonesia. The study focuses on net profit margin (NPM), return on equity (ROE) and good corporate governance (GCG) as potential determinants. The research population comprises 20 SOE companies registered at the Indonesia Stock Exchange (IDX) from 2017 to 2022. The purposive sampling method is employed to select a sample of 6 companies that meet the specific criteria outlined in the research objectives. Panel data regression with common effects is used as the research technique. The results reveal that net profit margin (NPM) and return on equity (ROE) do not exert a significant impact on the stock returns of SOE companies listed on the IDX. However, good corporate governance (GCG) is identified as a strong negative factor influencing the stock returns of these companies. The findings suggest that investors and stakeholders should carefully consider the role of good corporate governance (GCG) when evaluating and making decisions related to state-owned enterprises (SOE) stocks in the Indonesian market. Implementing robust governance practices may be crucial for mitigating potential negative effects on stock returns. The practical implications of these findings emphasize the need for policymakers, regulators and company management to enhance GCG practices to enhance overall performance and sustain investor trust in SOE stocks.